2010
DOI: 10.1093/abbs/gmq087
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant linear B-cell epitopes within the major outer membrane protein of <italic>Chlamydia trachomatis</italic>

Abstract: Chlamydia trachomatis is one of the most prevalent sexually transmitted pathogens. Chlamydial major outer membrane protein (MOMP) can induce strong cellular and humoral immune responses in murine models and has been regarded as a potential vaccine candidate. In this report, the amino acid sequence of MOMP was analyzed using computer-assisted techniques to scan B-cell epitopes, and three possible linear B-cell epitopes peptides (VLKTDVNKE, TKDASIDYHE, TRLIDERAAH) with high predicted antigenicity and high conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Other than helping to focus on and thereby narrowing down the specificity of immune response, they also leave room for chimera generation including multiple epitopes from same as well as different and slightly more immunogenic antigens. Though epitopes can be linear or conformational, Zhu et al (2010) have demonstrated the immunodominance of linear epitopes in the past. Therefore, in the present study, we have attempted to predict linear B cell epitopes and analyze their ability to evoke focused immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than helping to focus on and thereby narrowing down the specificity of immune response, they also leave room for chimera generation including multiple epitopes from same as well as different and slightly more immunogenic antigens. Though epitopes can be linear or conformational, Zhu et al (2010) have demonstrated the immunodominance of linear epitopes in the past. Therefore, in the present study, we have attempted to predict linear B cell epitopes and analyze their ability to evoke focused immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Such vaccines provide many advantages over the conventional subunit vaccine approach including instigating a focused immune response, the facility to engineer epitopes in order to customize the type of immune response required, ease of synthetic preparation on a large scale, and the ability to add additional immunogenicity and stability-enhancing groups (carbohydrates, lipids, phosphate groups) (van der Burg et al 2006;Purcell et al 2007). B cell and T cell epitope-based vaccines have been successful against a variety of pathogens including viruses (Depla et al 2008;Sun et al 2013), bacteria (Zhu et al 2010;Xu et al 2011;Li et al 2012), and parasites (Nardin et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several peptides containing both HLA and H2 restricted cytotoxic T-lymphocyte (CTL)/Th epitopes were screened by analyzing the amino acid sequence of Ct MOMP, from which the peptide of MOMP 370-387 containing the reported B-cell epitope (TRLIDERAAH) [ 13 ] was selected to be a candidate for MOMPm (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…This recombinant approach was subsequently used to produce GVNPs displaying three different outer-membrane proteins from Chlamydia trachomatis [66]. These proteins were: the major outer membrane protein (MOMP), outer membrane complex B (OcmB) and polymorphic outer-membrane protein D (PompD), each of which have been proposed to have roles in the virulence of C. trachomatis and have been suggested as potential vaccine candidates [67][68][69]. Western blots performed using anti-GvpC and anti-Chlamydia antibodies, as well as sera from patients with Chlamydia infections, were used to detect the presence of MOMP, PompD and OcmB fragments on the surface of the GVNPs [66].…”
Section: The Use Of Gas Vesicles In Engineering Vaccinesmentioning
confidence: 99%